Electrical Studies of Carboxy Methycellulose-Chitosan Blend Biopolymer Doped Dodecyltrimethyl Ammonium Bromide Solid Electrolytes - Nur Yasmin Abu Bakar; Nur Hafiza Mr. Muhamaruesa; Nur Ain Bashirah Aniskari; Mohd Ikmar Nizam Mohamad Isa (Science Publications, 2024)
In this study, a polymer-blend system consist of Carboxy Methylcellulose (CMC)-Chitosan (CS) as blend biopolymer host and doped with various composition of Dodecyltrimethyl Ammonium Bromide (DTAB) were successfully prepared via solution casting techniques. The new system has been analyzed through Electrical Impedance Spectroscopy (EIS) from temperature 303 K until 393 K to determine the conductivity of biopolymer electrolytes in the frequency range of 50 Hz to 1 MHz and the voltage between 5 to 50 mV. The optimum conductivity (1.86×10?6 S.cm?1) at ambient temperature obtained for composition of 5 wt.% DTAB. The temperature dependence of ionic conductivity was found to obeys the Arrhenius rule where R2?1 and thermally activated. The dielectric studies show a non-Debye behavior of SBEs based on the analyzed data using complex permittivity, e* and complex electrical modulus, M* of the sample at selected temperature.